The reproach of modalism: a difficulty for Karl Barth's doctrine of the trinity - Jowers, Dennis William (Scottish journal of theology, 2003)
Though renowned for restoring the dogma of the trinity to a place of honor in Protestant dogmatics, Karl Barth has faced widespread criticism for allegedly introducing an ancient heresy into that very doctrine: the heresy of modalism. In this paper, we analyze: (a) Barth's doctrine of the trinity as presented in his Church Dogmatics I/1; (b) the arguments Barth himself employs against modalism; and (c) those aspects of Barth's doctrine of the trinity which, is his critics' view, commit him to some form of modalism. On this basis, we argue that Barth, in spite of infelicities and even errors in his doctrine of the trinity, does not in any way endorse the heresy of modalism.